Global linear and nonlinear gyrokinetic modelling of Alfvén eigenmodes in ITER. (22nd February 2021) - Hayward-Schneider, T.; Lauber, Ph.; Bottino, A.; Lu, Z.X.
Abstract: Linear and nonlinear modelling of Alfvénic instabilities, most notably toroidal Alfvén eigenmodes (TAEs), obtained by using the global nonlinear electromagnetic gyrokinetic model of the code ORB5 are presented for the 15 MA scenario of the ITER tokamak. Linear simulations show that elliptic Alfvén eigenmodes and odd-parity TAEs are only weakly damped but not excited by alpha particles, whose drive favours even-parity TAEs. Low mode number TAEs are found to be global, requiring global treatment. Nonlinearly, even with double the nominal EP density, single mode simulations lead to saturation with negligible EP transport however multi-mode simulations predict that with double the nominal EP density, enhanced saturation and significant EP redistribution will occur.